A Review Paper on Transport and Climate Change (International Journal of Innovative Research in Engineering & Management, 2023)
Automobile emits 26% of global CO2  and is among the select sectors whose pollution are  continually rising. Cars, road commerce, and aircraft are  the three primary sources of greenhouses gas pollutants  from the communication industry, and this research  focusses on ways to reduce pollutants from these three  key categories. A review of emerging technology, such as  alternate transportation fuels. It is suggested that technical  innovation be used to remove the reliance on petroleum,  but it seems that this is unlikely to be the only solution  the issue of climate change To attain a stable level of  greenhouse gas emissions from transportation, people  must alter their habits. It will also be necessary to have a  policy. Policymakers are under increasing pressure to  address climate change in order to provide sustainable  transportation. Although there is a tendency to  concentrate on long-term technical solutions, short-term  behavioural modification is critical if long-term  technological solutions are to be implemented. The  advantages of modern technology must be properly  appreciated.
Keywords: Aviation; Behavioural Change; Climate Change; Technological; Transport